EKSISTENSI ISTIHSAN SEBAGAI DALIL ISTINBATH FIQH SIYASAH - Henderi Kusmidi (Fakultas Syari'ah Universitas Islam Negeri Fatmawati Sukarno Bengkulu, 2021)
Abstract: This study aims to comprehensively describe the existence of istihsan in siyasa fiqh. There are some scholars who reject the existence of istihsan as one of the methods of istinbathul ahkam, this group believes that the use of istihsan in istinbathul ahkam is not valid, especially in matters of fiqh siyasah. The reason for this refusal is based on the concern that the door of ijtihad will be opened based on mere lust. This happens because the istihsan method is not yet clearly standardized for its implementation. However, what actually happened in the field was not like that. Based on the research that the author did, it was found a conclusion that istihsan really exists and exists in the world of istinbathul ahkam explicitly and exists in siyasah fiqh implicitly. This happens because istihsan is responsive to the problems of social life, as well as progressive, in harmony and in line with the Qur'an and the hadith of the Prophet Muhammad. Keywords: Dalil, Fiqh Siyasah, Istihsan.